Pengaruh Good Corporate Governance dan Ukuran Perusahaan terhadap Profitabilitas pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Nanda Maratus Solikha; Ni Luh Putu Sri Purnama Pradnyani; Eka Putri Suryantari (Jurnal Widya Akuntansi dan Keuangan, 2023)
The financial sector's ability to profit was hampered during the Covid-19 pandemic. General Operating Procedures (or GCG) are a set of rules by which a company or other organization conducts its day-to-day business. This study aims to examine the relationship between the audit committee, board of directors, board of commissioners, and company size as surrogates for good corporate governance and the financial performance of Indonesian banking firms traded on the Indonesia Stock Exchange. Purposive sampling was used, and the resulting sample size was 48 observations. SPSS 20 for Windows is used for multiple linear regression analysis, a type of data analysis. GCG has a positive effect on bank profitability, according to studies, and is proxied by the board of directors, the audit committee, and the board of commissioners. Financial success at IDX-listed banks is positively correlated with company size. Keyword: Bank;Good Corporate Governance; Profitability